RETURN ON ASSET SEBAGAI PEMEDIASI HUBUNGAN ANTARA CAPITAL ADEQUACY RATIO, LOAN TO DEPOSIT RATIO, NON PERFORMING LOAN DAN DEBT TO EQUITY RATIO TERHADAP NILAI PERUSAHAAN PADA SEKTOR PERBANKAN - YESHA NU'MA ARULA PUTRI; Dwi Eko Waluyo (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study aims to analyze the role of return on assets (ROA) as a mediator in the relationship between capital adequacy ratio (CAR), loan-to-deposit ratio (LDR), non-performing loans (NPL) and debt-to-equity ratio (DER) on the value of banking companies as measured by price to book ratio (PBV). The data used comes from the financial statements of banks listed on the Indonesia Stock Exchange. Methods: The analysis was conducted using the regression method with a mediation testing approach. Results: The results showed that CAR and NPL have a significant negative effect on ROA, while LDR has a significant positive effect on ROA. As for DER, it has no significant effect on ROA. Furthermore, CAR has a significant positive effect on PBV, while LDR, NPL, and DER have no significant effect on PBV. ROA itself has a significant negative effect on PBV, this indicates that increasing profitability does not always increase the value of companies in the banking sector. The mediation test results show that CAR and NPL play a role in increasing firm value through ROA, while LDR and DER do not have a strong enough influence on the relationship.